PROFITABILITY OF PRODUCTION OF PASTA FROM SPELT FLOUR - Vukoje, Veljko; Psodorov, Đorđe; Živković, Jasmina (Economics of Agriculture, 2013)
This paper analyzes the most important parameters for profitability of production of pasta made from spelt flour produced in an organic farming system. Research pertains to plant of medium capacity which is also suitable for construction on family agricultural households. In order to obtain a more reliable assessment of profitability, the comparison is performed with the production of wheat flour pasta. Comparative analysis of the profitability level is based on analytical calculations of production and additional derived indicators. The main raw material, spelt flour, dominates the total costs with 59.4% (whereas for wheat flour it is 37.5%). As expected, significant share of cost is assigned to labor (12.9%), as well as fixed costs (12.4), while energy has a relatively small share (4.6%). Assuming that the high level of productivity is achieved, the average wholesale price of about € 2.11 per kilo provides an annual income of € 30,766.00 (whereas annual income for wheat is € 12,260.00). Taking into account a solid economy ratio (1.32) and payback period of investment (6.9 years), it is evident that this can be a very profitable business.